How to make your man commit and what to do if he won't - West-Meads, Zelda (Hodder & Stoughton, 1999)
Using first-hand accounts and 20 years of experience as a relationship counsellor, the author of this book explains why some men find it so hard to commit, how to allow trust to build into a truly committed relationship, and how to help others overcome their fears of commitment.